Architectures for person to person communications in disaggregated networks - ARGYROUDIS, PATROKLOS; DOYLE, LINDA; O'MAHONY, DONAL EDWARD (IEEE, 2006)
Current telecommunications systems allocate identifiers to devices, and end-points. While this has worked well thus far, we believe that as more devices are used to access these systems, people have a tendency to be mobile across these devices. In this article we review current systems and introduce a new model for telecommunications, which we term person to person communications. Under this new model people are allocated identifiers, which they may associate with any number of devices. We outline why we believe this to be a more effective model than the current one
PUBLISHED
Keywords: identifiers; networks